Rectangular Array Multicore Fiber Realizing Low Crosstalk Suitable for Next-Generation Short-Reach Optical Interconnects With Low Misalignment Loss - Jitendra K. Mishra; B. M. A. Rahman; Vishnu Priye (IEEE Photonics Journal, 2016)
Toward the next-generation exa-scale short-reach optical interconnects (OIs) supporting large-capacity data transmission, a compact computer-compatible 8-core heterogeneous trench-assisted multicore fiber (TA-MCF) is proposed, in which cores are arranged in a rectangular array. To analyze the crosstalk (XT) between adjacent cores of TA-MCF OI, a rigorous full-vectorial $H$ - field finite element method (FEM) and coupled power theory are applied. The impact of various trench design parameters on the mode-coupling coefficient $C_{mn}$ and the coupling length $L_{c}$ is discussed in detail. An accurate explicit condition for the achievement of low XT in an 8-core heterogeneous TA-MCF OI is obtained through numerical simulations. A rigorous modal solution approach based on the computationally efficient FEM and the least squares boundary residual method is employed to analyze the coupling loss caused by the misalignment to a butt-coupled TA-MCF OI.